DESAIN BUKU CERITA OMPUNG SILAMPONGA UNTUK GENERASI Z MELALUI INSTAGRAM CAROUSEL - Muryasari, Desiana; Widarta, Widarta (Institut Bisnis dan Teknologi Indonesia, 2024)
Folk tales that embody local wisdom hold rich cultural and traditional value. However, they are often less appealing to Generation Z. Having grown up in the digital era and being exposed to global culture, Generation Z tends to be more drawn to modern and international content. They spend a significant amount of time in the digital world, particularly on social media. Therefore, social media can serve as an effective strategy for introducing folk tales and local wisdom to Generation Z. This study focuses on designing illustrated stories that both entertain and educate Generation Z about folk tales and local wisdom through a Carousel format on the Instagram platform. Data for this study were collected through observation, interviews, documentation, and literature review. The design methodology employed is Design Thinking, which involves five key stages: empathize, define, ideate, prototype, and test. The outcome of this study is the illustrated story